Conversations about transcultural European memory Pokalbiai apie transkultūrinę Europos atmintį - Kavaliauskas, Tomas (editor) (Vytautas Magnus University, 2014)
It is a book of conversations in which distinguished scholars share their insights on transcultural memory, European languages, the evil of communism and forgiveness. Cross-regional comparisons of memory and cultural identity issues should give the reader the feeling of transnational altitudes, while preserving the taste of regional and national specifics: Latvian, Lithuanian, Polish, Russian, Czech, Hungarian, Romanian, Bulgarian, Ukrainian, Slovenian, Norwegian, Swedish and Swiss.